Non-Operative Management of Pancreatic Pseudocyst in Paediatric Population: A Case Report - Safaa Al-Atrash (AlQalam Journal of Medical and Applied Sciences, 2024)
Pancreatic pseudocyst is a rare medical condition in the pediatric population; it is a challenging lesion to diagnose and treat. The most common etiology identified in children is post-traumatic, being up to 80-100% of the cases. Approximately 60% of pancreatic pseudocysts following trauma require surgical intervention. The pseudocyst of the pancreas develops within the first 3–4 weeks after trauma. In this report, we present a case of a 3-year-old boy with pancreatic pseudocyst followed by blunt abdominal trauma in which successful conservative management was done without any complications or need for surgical intervention. This case differs from most cases reported in the literature because of the short time between pancreatic trauma and pseudocyst formation. Furthermore, the successful non-operative management of grade III-IV pancreatic injury with acute formation of pseudocyst. تُعد الكيسة الكاذبة البنكرياسية حالة طبية نادرة في فئة الأطفال؛ وهي آفة صعبة التشخيص والعلاج. السبب الأكثر شيوعًا الذي تم تحديده لدى الأطفال هو ما بعد الصدمة، حيث يصل إلى 80-100% من الحالات. يتطلب ما يقرب من 60% من الأكياس الكاذبة البنكرياسية بعد الصدمة تدخلًا جراحيًا. تتطور الكيسة الكاذبة البنكرياسية في غضون الأسابيع الثلاثة إلى الأربعة الأولى بعد الصدمة. في هذا التقرير، نقدم حالة صبي يبلغ من العمر 3 سنوات يعاني من كيس كاذب في البنكرياس متبوعًا بصدمة بطنية حادة تم فيها إجراء علاج محافظ ناجح دون أي مضاعفات أو الحاجة إلى تدخل جراحي. تختلف هذه الحالة عن معظم الحالات المذكورة في الأدبيات بسبب الوقت القصير بين الصدمة البنكرياسية وتكوين الكيسة الكاذبة. علاوة على ذلك، فإن العلاج غير الجراحي الناجح لإصابة البنكرياس من الدرجة الثالثة والرابعة مع التكوين الحاد للكيس الكاذب